Development of a Web-Based System for PSM Supervision - Wan Fauzi, Wan Nor Fatini; Alduais, Nayef Abdulwahab Mohammed (Applied Information Technology And Computer Science, 2025)
PSM supervision system is a web-based system that was developed to manage PSM supervision. It allows the student to select their potential supervisor from the system and can check the availability of the supervisor. The supervisor can track the progress of the student with the report submission features in the system. Waterfall model was used for the development of the system.This system was developed with technologies such as HTML, CSS, JavaScript, and PHP code which was written using Visual Studio Code. System testing which are test plans for each module and user acceptance testing (UAT) has been conducted for the system to ensure the system meets its requirements. Based on the testing, the feedbacks from the target user mostly shown that they satisfied with the functionality and interface of the system. In future, the system should added with more advanced features such as real-time chat between student and supervisor functionality.